Anti-islanding algorithm based on active phase jump with positive feedback and intermittent perturbation for integration of inverter-based distributed energy resources to the electric power system. - Resende, Ênio Costa (2024)
The growing penetration of Distributed Generation Systems (DGS) based on renewable resources into the distribution utility grid paves the way for a new energy generation and for an electrical consumption paradigm founded on the gradual replacing of fossil fuels by clean power generation. However, in spite of all its benefits, the adoption of the DGS brings new problems and challenges that must be addressed by the academical research. One of the main security issues is the unintentional islanding. Defined as the loss of the connection with the main grid, the unintentional islanding phenomenon can lead to the increasing of the harmonic pollution of the grid, electrical accidents with maintenance workers and out-of-phase reclosures. The purpose of this work is to present a new Anti-Islanding Protection (AIP) algorithm, based on the insertion of a phase jump at the beginning of each half cycle of the inverter output current. This phase jump will be parametrized with a positive frequency feedback in order to improve the algorithm performance by linking the frequency error with the inserted disturbance. Futhermore, the new AIP scheme defines maximum and minimum frequency alarm thresholds that, when reached, trip an additional phase jump to improve islanding detection, reducing the detection time and mitigating the Non-Detection Zone (NDZ) without demanding extra current harmonic degradation. Beyond this, the work also performs a complete review of the islanding theory, addressing the NDZ concept and its mapping technologies and conducting a critical analysis of the already existing solutions, highlighting the evolution timeline of each algorithm. Finally, in order to attest the new solution effectivity, it will be also carried out a comparative study with other already known AIP methods: Active Frequency Drift (AFD), AFD by (CHEN et al., 2013), AFD with Pulsating Chopping Factor (AFDPCF), Sandia Frequency Shift (SFS) and the Active Phase Jump with Positive Feedback (APJPF). The test methodology will be based on the most restrictive Standards recommendations and the results will be categorized according to three Key Parameter Indicators (KPI): detection time, NDZ and THDi. The obtained results show that the proposed scheme reached the mitigation of the NDZ and accomplished the fastest islanding detection for all of the tested cases.